THE EFFECT OF GOOD CORPORATE GOVERNANCE, PROFITABILITY, AND COMPANY ACTIVITIES ON THE DISCLOSURE OF SUSTAINABILITY REPORT - Kurnia Heriansyah; Safila Faradiza (Jurnal Multidisiplin Sahombu, 2023)
This study aims to find out and provide empirical evidence of the effect of good corporate governance which is proxied by the independent board of commissioners and audit committees, profitability and company activities on sustainability report disclosure in LQ45 Non-Financial companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020 This research is a quantitative study with a total sample of 8 companies. The selected companies used a purposive sampling technique based on predetermined criteria. The data used is secondary data in the form of annual reports and sustainability reports for the 2016-2020 period obtained from the official website of the Indonesia Stock Exchange or the website www.idx.co.id. The results of this study partially show that the independent board of commissioners has an effect on the disclosure of the sustainability report. the audit committee influences the disclosure of the sustainability report. profitability affects the disclosure of the sustainability report. And the company's activities affect the disclosure of sustainability reports